Visual Vision, and their relationship in the performance of high- Spike Diagonal and rectum skill accuracy Volleyball - Sabhan, Hussein; Abedulhussein, Dena (Journal of Physical Education, 2015)
That visions of capabilities that help in the success and development of performance skills of volleyball players, Clarity field of view, minute, contribute to finding appropriate solutions for different situations play and observation, and that player Spike higher crushing it Note, inter alia, blocking, and the movement of players defenders of the opposing team , and the movement of the player setter colleague, and direction of the ball, speed and height, as well as the proper and timely with the speed and height of the coming of the players prepared for the ball, so is the importance of research to find a relationship between the beating of higher overwhelming the country and rectum visual and vision to the players, and I aim of the study: to identify the relationship visions, in the performance of beating higher overwhelming the country and rectum skill accuracy Volleyball for young people, either impose Search: There are significant differences between the visual and accurate vision relationship performance beating higher overwhelming the country and rectum skill Volleyball for young people, the researcher using the descriptive manner of mutual relations, was chosen the research community way intentional and represented my players clubs Baghdad for youth season (2014_2015), the research sample Vtm selected way intentional illusion players clubs Baghdad (Acharth_ Industry) totaling (24) and aged (16-18 years), were excluded player prepared number (2) free and the player number (2), and accounted for (28.14%) of the original community, and I've concluded researcher and there is a high correlation between the visions, skill beating higher overwhelming the country and rectum in 4 center, and through the conclusions we recommend attention trainers exercises visions, and give it time enough in training modules, the use of training means to develop visions and linked technical skills in volleyball